Gonadal function in males with autoimmune Addison's disease and autoantibodies to steroidogenic enzymes. (24th April 2014) - Dalla Costa, M; Bonanni, G; Masiero, S; Faggian, D; Chen, S; Furmaniak, J; Rees Smith, B; Perniola, R; Radetti, G; Garelli, S; Chiarelli, S; Albergoni, M P; et al.
Summary: Steroidogenic enzyme autoantibodies (SEAbs) are frequently present and are markers of autoimmune premature ovarian failure (POF) in females with autoimmune Addison's disease (AAD). The prevalence and significance of SEAbs in males with AAD have not yet been defined. We studied the prevalence of SEAbs in a large cohort of males with AAD and assessed the relationship between SEAbs positivity and testicular function. A total of 154 males with AAD (mean age 34 years) were studied. SEAbs included autoantibodies to steroid-producing cells (StCA), detected by immunofluorescence, and steroid 17α-hydroxylase (17α-OHAbs) and side chain cleavage enzyme (SCCAbs) measured by immunoprecipitation assays. Gonadal function was evaluated by measuring follicle-stimulating hormone (FSH), luteinizing hormone (LH), total testosterone (TT), sex hormone-binding globulin (SHGB), anti-müllerian hormone (AMH) and inhibin-B (I-B). Twenty-six males, 10 SEAbs (+) and 16 SEAbs (–), were followed-up for a mean period of 7·6 years to assess the behaviour of SEAbs and testicular function. SEAbs were found in 24·7% of males with AAD, with the highest frequency in patients with autoimmune polyendocrine syndrome type 1 (APS-1). The levels of reproductive hormones in 30 SEAbs (+) males were in the normal range according to age and were not significantly different compared to 55 SEAbs (–) males ( P  > 0·05). During follow-up, both SEAbs (+) and SEAbs (–) patients maintained normal testicular function. SEAbs were found with high frequency in males with AAD; however, they were not associated with testicular failure. This study suggests that the diagnostic value of SEAbs in males with AAD differs compared to females, and this may be related to the immunoprivileged status of the testis.